A Novel Germline Heterozygous BCL11B Variant Causing Severe Atopic Disease and Immune Dysregulation - Lu, Henry Y.; Sertori, Robert; Contreras, Alejandra V.; Hamer, Mark; Messing, Melina; Del Bel, Kate L.; Lopez-Rangel, Elena; Chan, Edmond S.; Rehmus, Wingfield; Milner, Joshua D.; McNagny, Kelly M.; Lehman, Anna; et al. (Frontiers in Immunology, 2021)
B cell lymphoma/leukemia 11B (BCL11B) is a C2H2 zinc finger transcription factor that is critically important for regulating the development and function of a variety of systems including the central nervous system, the skin, and the immune system. Germline heterozygous variants are associated with a spectrum of clinical disorders, including severe combined immunodeficiency as well as neurological, craniofacial, and dermal defects. ~50% of these individuals present with severe allergic disease. Here, we report the detailed clinical and laboratory workup of one of the most severe BCL11B-dependent atopic cases to date. Leveraging a zebrafish model, we were able to confirm a strong T cell defect in the patient. Based on these data, we classify germline BCL11B-dependent atopic disease as a novel primary atopic disorder.